1995
DOI: 10.1097/00003246-199504000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative enteral nutrition with arginine-omega-3 fatty acids and ribonucleic acid-supplemented diet versus placebo in cancer patients

Abstract: Supplementation of enteral diet with arginine, RNA, and omega-3 fatty acids in the early postoperative time period improves postoperative immunologic responses and helps to overcome more rapidly the immunologic depression after surgical trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
10

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(88 citation statements)
references
References 12 publications
4
74
0
10
Order By: Relevance
“…68 Arginine is important for activation of T lymphocytes, promotion of T-helper cells, phagocytosis, and respiratory burst generation. 69 Arginine serves as a precursor to nitric oxide and proline; both are important to anastomotic and wound healing-nitric oxide promotes vasodilation and tissue oxygenation while proline contributes to collagen deposition during healing. The omega-3 fatty acids docosahexaenoic acid and eicosapentaenoic acid play a wide range of anti-inflammatory roles, reducing oxidative injury, down-regulating arachidonic acid, and generating resolvins.…”
Section: Role Of Perioperative Imnmentioning
confidence: 99%
“…68 Arginine is important for activation of T lymphocytes, promotion of T-helper cells, phagocytosis, and respiratory burst generation. 69 Arginine serves as a precursor to nitric oxide and proline; both are important to anastomotic and wound healing-nitric oxide promotes vasodilation and tissue oxygenation while proline contributes to collagen deposition during healing. The omega-3 fatty acids docosahexaenoic acid and eicosapentaenoic acid play a wide range of anti-inflammatory roles, reducing oxidative injury, down-regulating arachidonic acid, and generating resolvins.…”
Section: Role Of Perioperative Imnmentioning
confidence: 99%
“…In a previous postoperative study of patients with cancer who were fed an immune-enhancing diet, Daly et al 3 observed no effect of immunonutrition on the first postoperative day and a significant improvement as of day 7. Similarly, in a postoperative study 5 from our group in patients who underwent surgery for upper gastrointestinal tract cancer, early postoperative immunonutrition resulted in significant advantage of humoral and cellular immunity compared with the control feed after 1 week of treatment. These beneficial immunological changes were associated with an overall reduction of infec-tious complications in the extended clinical outcome study, but the improved outcome was not significant before 5 days after surgery.…”
mentioning
confidence: 68%
“…It seems, therefore, that even early and aggressive application of enteral immunonutrition after surgery is not sufficient to prevent the immunosuppression that takes place in the early postoperative period. In a previous postoperative study 5 of patients with cancer who were fed an immune-enhancing diet, a significant improvement of humoral and cellular immune variables was not observed until 1 week of treatment. By contrast, perioperative administration of an 3 FA-, arginine-, and RNA-nucleotides-enriched enteral formula for 7 days preoperatively and in the postoperative period significantly improved postsurgical immunosuppressive and inflammatory responses and gut function.…”
Section: Commentmentioning
confidence: 84%
“…Enteral nutritionp rovides the intestinal mucosa with nutrients, and maintains the gut-associated lymphoid tissue (GALt), which may reduce bacterial translocation (8, 9). In many early studiesperioperative administration of immune-enhancing formulas has shown to improve gut function and posi-tivelym odulate postsurgical immunosuppressive and inflammatory responses (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%